2017
DOI: 10.1016/j.clml.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bosutinib Treatment on Renal Function in Patients With Philadelphia Chromosome-Positive Leukemias

Abstract: Long-term bosutinib treatment is associated with an apparently reversible decline in renal function with frequency and characteristics similar to renal decline observed with long-term imatinib treatment. Patients with risk factors for Grade ≥ 3b eGFR should be monitored closely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…Increased blood creatinine (any grade) had a higher incidence in years 3 and 4 (5% each) versus years 1 (2%) and 2 (1%) in the CP 2L cohort and in year 4 (13%) versus years 1 (7%), 2 (4%), and 3 (3%) in the CP 3L cohort [ 5 , 9 ]. However, recently published results suggest that the decline in renal function associated with long-term bosutinib treatment is reversible and similar in frequency and characteristics to that observed with long-term imatinib [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increased blood creatinine (any grade) had a higher incidence in years 3 and 4 (5% each) versus years 1 (2%) and 2 (1%) in the CP 2L cohort and in year 4 (13%) versus years 1 (7%), 2 (4%), and 3 (3%) in the CP 3L cohort [ 5 , 9 ]. However, recently published results suggest that the decline in renal function associated with long-term bosutinib treatment is reversible and similar in frequency and characteristics to that observed with long-term imatinib [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bosutinib has been associated with a decrease in glomerular filtration rate that is typically modest and potentially reversible (similar to what has been reported with imatinib). 19 , 20 Dose adjustments are recommended in patients with baseline and treatment-emergent renal impairment. 6 , 19 Careful monitoring, supportive care, and prompt management of toxicities may allow patients to continue treatment long term.…”
Section: Discussionmentioning
confidence: 99%
“…Renal AE data has not yet been reported for the BFORE trial [6]. In an analysis of the phase 1/2 study and the BELA trial, renal AEs were reported in 52/403 patients with CP-CML (13%) receiving ≥ 2L bosutinib, and in 22/248 (9%) receiving 1L bosutinib, over a follow-up of at least 48 months [30]. The most common renal AE in both studies was increased blood creatinine (in 10% of the ≥ 2L patients and 6% of the 1L patients) [30].…”
Section: Recommendations For Managing Aes Following Treatment With Bomentioning
confidence: 99%